Curcumin as a protective agent against chromium and ammonia toxicity using molecular and biochemical approaches in fish - Amir Najir Mulla; Supriya Tukaram Thorat; Kalpana Chandramore; Prem Kumar; Kotha Sammi Reddy; Neeraj Kumar (Scientific Reports)
Abstract In aquatic ecosystems, metal and ammonia pollution pose major concern as they contaminate the environment and induces toxicity in fish. The present study addresses the toxicity induced by chromium (Cr) and ammonia (NH3) toxicity in fish and investigates the potential of dietary curcumin in mitigating the effects of concurrent exposure to theses stressors in Pangasianodon hypophthalmus. Three isonitrogenous and isocaloric diets were formulated: a control diet (0% curcumin) and two curcumin-supplemented diets containing 0.1% and 0.2% curcumin. Four experimental groups were designed in a completely randomized design: (1) control, (2) concurrent exposure to Cr and NH3 toxicity and fed with control diet, (3) 0.1% curcumin with Cr and NH3 exposure, and (4) 0.2% curcumin with Cr and NH3 exposure. Fish fed with 0.2% curcumin diet, followed by the 0.1% curcumin diet under Cr and NH3 stress, exhibited significantly reduced cortisol levels compared to the control and Cr + NH3 groups. Similarly, the expression of HSP70 and iNOS genes in liver tissue was significantly downregulated in the 0.1% and 0.2% curcumin-fed groups compared to other groups. Concurrent exposure to Cr and NH3 led to a considerable increase in oxidative stress enzyme in liver and kidney tissues, including glutathione S-transferase (GST), catalase (CAT), and superoxide dismutase (SOD). However, dietary supplementation with 0.1% curcumin significantly reduced oxidative stress enzyme activities. The stressors markedly reduced acetylcholinesterase (AChE) activity, but supplementation with 0.1% curcumin restored AChE activity. The expression of stress-related genes such as cytochrome P450 (CYP450), caspase-3a (Cas3a), and tumor necrosis factor-alpha (TNF-α) was noticeably downregulated in the curcumin-fed groups, reducing the impact of Cr + NH3 stress. Furthermore, total immunoglobulin (Ig) levels and growth-related gene expression, including growth hormone (GH) and growth hormone receptor 1 (GHR1), were significantly upregulated in the 0.1% curcumin-fed group under Cr + NH3 stress compared to all other groups. Additionally, myostatin (MYST) gene expression was significantly downregulated in the 0.1% curcumin-fed group. Activities of cellular metabolic and digestive enzymes were significantly improved with curcumin supplementation, mitigating the adverse effects of Cr + NH3 stress compared to the control and other groups. Moreover, Cr bioaccumulation in different fish tissues was reduced in the 0.1% curcumin-fed group. This study highlights the potential of dietary curcumin in mitigating the adverse effects of concurrent Cr and NH3 exposure through gene regulation, thereby improving the physiological and productive performance of Pangasianodon hypophthalmus.